“implementación de una plataforma e-learning para mejorar la gestión académica en el nivel secundario del colegio privado carmelitas de la ciudad de trujillo” - Navarro Reyes, Jean Estuardo (2016)
The present qualified work of investigation "IMPLEMENTATION OF E-LEARNING PLATFORM FOR IMPROVING THE ACADEMIC LEVEL MANAGEMENT IN PRIVATE SECONDARY SCHOOL CARMELITAS ONES OF THE CITY OF TRUJILLO", has evaluated the characteristics of the development of the most relevant processes of the institution in study, problems being observed as the lack of diffusion of the web page, scanty didactic content in the portal Web, traditional use of informative means, unnecessary expenses of material for the diffusion of information, between others; of which was observed that deficiency in the Management of Information of the institution, of which it is not achieved to expire in its entirety with the goals that are planned. Our project seeks to improve the Management of Information across the construction of a e-learning platform for the secondary level, of which one expects to optimize the number of informative means that academic information of the pupil publishes, to satisfy the pupils empowered with regard to the information who receive, to reduce the time of search of information, between others. Of this form, the institution will be able to create competitive advantages to comparison of other institutions of the same item, in addition the institution possesses the technological support for the accomplishment of our project. For the development there will be in use the Methodology of Process Unified of Development of Software (RUP), since it is the methodology that is in use mainly in projects similar to our one, good results being obtained, in addition we possess the experience necessary for its accomplishment.